Serum levels of Vanin-2 increase with obesity in relation to inflammation of adipose tissue and may be a predictor of bariatric surgery outcomes - Geng, Shan; Chen, Dongmei; Wang, Yanping; Yu, Xingrui; Zuo, Dan; Lv, Xinlu; Zhou, Xuelian; Hu, Chengju; Yang, Xuesong; Ma, Xujue; Hu, Wenjing; Xi, Jiazhuang; et al. (Frontiers in Nutrition, 2023)
Objective Excessive obesity can lead to dysfunction in adipose tissue, which contributes to the development of comorbidities associated with obesity, such as type 2 diabetes (T2D), cardiovascular and cerebrovascular disease, among others. Previous research has mainly focused on the Vanin family in systemic inflammatory diseases or predicting its role in tumor prognosis, while neglecting its role as a secretory protein in adipose tissue inflammation and metabolism. The objective of this study was to compare the changes in Vanin-2 levels in the circulating blood of normal and obese individuals, and to assess its correlation with inflammatory factors in vivo. Furthermore, the study aimed to systematically evaluate its effectiveness in human weight loss surgery. Methods Serum concentrations of Vanin-2 and inflammatory indicators were measured in 518 volunteers. Furthermore, the concentrations of Vanin-2 were measured both before and after weight loss through a dietetic program or laparoscopic sleeve gastrectomy (LSG). Additionally, we assessed the levels of insulin, adiponectin, and inflammation-related factors. The hormonal profile and changes in body weight were evaluated at baseline and 3 months after surgery. Results Serum levels of Vanin-2 were found to be significantly increased in individuals with overweight/obesity (OW/OB) group (controls 438.98 ± 72.44, OW/OB 530.89 ± 79.39 ug/L; p < 0.001). These increased levels were associated with IL-18, BMI, FAT%, and HOMA-IR. However, levels of Vanin-2 remained unchanged after conventional dietary treatment. On the other hand, weight loss induced by LSG resulted in a significant decrease in Vanin-2 concentrations from 586.44 ± 48.84 to 477.67 ± 30.27 ug/L (p < 0.001), and this decrease was associated with the Vanin-2 concentrations observed before the operation. Conclusion Serum Vanin-2 is a highly effective biomarker for assessing adipose tissue inflammation in obesity and has the potential to serve as a predictor of bariatric surgery outcomes.